2021
DOI: 10.29020/nybg.ejpam.v14i1.3916
|View full text |Cite
|
Sign up to set email alerts
|

Global Hop Domination Numbers of Graphs

Abstract: A set S ⊆ V (G) is a hop dominating set of G if for each v ∈ V (G) \ S, there exists w ∈ S such that dG(v, w) = 2. It is a global hop dominating set of G if it is a hop dominatingset of both G and the complement of G. The minimum cardinality of a global hop dominatingset of G, denoted by γgh(G), is called the global hop domination number of G. In this paper, we study the concept of global hop domination in graphs resulting from some binary operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…It is shown that the absolute difference of these parameters can be made arbitrarily large. Further, we rectify a result found in [16] and use the corrected result to prove some results in this paper.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…It is shown that the absolute difference of these parameters can be made arbitrarily large. Further, we rectify a result found in [16] and use the corrected result to prove some results in this paper.…”
Section: Introductionmentioning
confidence: 81%
“…Shortly after Natarajan and Ayyaswamy [13] introduced and studied the concept of hop domination in a graph, some variants of the concept emerged. The concept and some of its variants are studied in [5], [11], [12], [15], and [16]. In this paper, we show that the standard domination and hop domination parameters are generally non-comparable.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Natarajan and Ayyaswamy [9] introduced and studied the concept of hop domination in graphs. Hop domination in graphs were also studied in [6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Natarajan et al [13] found characterization results for hop domination number equals other domination parameters like total domination number, connected domination number for several families of graphs. Many scholars have explored this parameter in the years thereafter, leading to novel versions such as connected hop domination, total perfect hop domination, Roman hop domination, Global hop domination, etc., [11,12,[15][16][17][18]20]. In 2018, Natarajan et al [14] discussed hop domination number for some special families of graph like central graph, middle graph and total graph.…”
Section: Introductionmentioning
confidence: 99%